Uma sequência didática para o ensino e aprendizagem das cevianas no nono ano do ensino fundamental II - Velozo, Carla Cristina Maia (2021)
Schools have been concerned with student performance, aggravated by the existence of students with age and grade distortions, which requires a little more attention among school segments regarding the search for solutions to alleviate poor performance in the Mathematics subject. This study aims to analyze the results obtained with the application of a didactic sequence in the development of teaching and student learning in relation to cevians. Regarding the methodology, it is a descriptive and explanatory research, and a case study carried out at the school located in the city of Osasco, with structured questionnaires, with the objective of building the concepts of cevianas and some notable points of a triangle. The research had the participation of students from the 9th year of Elementary School, classes A, B, C, D and E, through 6 questionnaires with subjective questions, which had the initial objective of identifying what the student already knows about the subjects to be worked on, an end to building the concept of cevians. The results showed the students ability to differentiate the cevians (height, median and bisector), their characteristics, in such a way that they are able not only to construct geometrically but also to conceptualize them with precision, as well as to understand the concept of height; Affirming the importance of perpendicularity. In addition to presenting greater knowledge of the subjects covered in the geometry classroom. It is therefore concluded that the participation of the teacher in this teaching-learning process as a mediator is important, he must be motivated so that, whenever possible, he can innovate in his classes.